Effect of residual interface stress on thermo-elastic properties of unidirectional fiber-reinforced nanocomposites - Chen, Y. Q.; Zhang, Z. G.; Huang, R. C.; Huang, Z. P. (International Journal of Mechanical Sciences, 2016)
Surface/interface effect plays a significant role in the study of the mechanical properties of nano composites. Most previous papers in the literature only considered the surface/interface elasticity, whereas some papers only considered the residual surface/interface stress (surface/interface tension). In this paper, an energy-based surface/interface theory is applied to systematically study the effective thermo-elastic properties of unidirectional fiber-reinforced nanocomposites, in which both the surface/interface elasticity and the residual surface/interface stress are included. The emphasis is particularly placed on the influence of the residual interface stress on the effective thermo-elastic properties of such nanocomposites, since this influence was ignored by many previous authors. Analytical expressions of five effective transversely isotropic elastic constants are derived, in which a modified generalized self consistent method is suggested to obtain an explicit expression of the size-dependent effective transverse shear modulus. Furthermore, with an introduced concept of 'equivalent fiber' (i.e., a fiber together with its interface), the effective thermal expansion coefficients and the effective specific heat at constant strain of the fiber-reinforced nanocomposite are obtained. Finally, numerical examples are illustrated, and the effect of residual interface stress on the effective thermo-elastic properties of the fibrous nanocomposite is discussed. It is shown that the residual interface stress has a significant effect on the overall thermo-elastic properties of the nanocomposites. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: composite-materials; connections; dependent elastic properties; effective moduli; effective specific-heats; effective thermo-elastic properties; fiber-reinforced nanocomposites; heterogeneous materials; inclusion; interface energy theory; modified generalized self-consistent method; nano-composites; residual interface stress; surface-tension; thin-films